Maternal blood pressures during pregnancy and the risk of delivering a small-for-gestational-age neonate. (2nd July 2016) - Block-Abraham, Dana M.; Adamovich, Dasha; Turan, Ozhan M.; Doyle, Lauren E.; Blitzer, Miriam G.; Baschat, Ahmet A.
ABSTRACT: Objective : To determine the relationship between maternal blood pressures throughout pregnancy and the risk of delivering a small-for-gestational-age (SGA) neonate. Methods : Women were prospectively enrolled at 9–14 weeks and had serial blood pressure measurements throughout pregnancy. SGA prevalence was compared to maternal blood pressure at enrollment, average blood pressure during each trimester, and blood pressure trends throughout gestation. Blood pressure was categorized as normotension, prehypertension, or hypertension using Joint National Committee on Hypertension-7 (JNC-7) definitions. Information on preeclampsia prevalence was also obtained due to its frequent concurrence with SGA. Results : A total of 758 women had 8438 blood pressure measurements taken (average 11.1, range 3–14) and 65 (8.6%) delivered an SGA neonate. Forty-two of 514 (8.2%) normotensive women at enrollment and 23/244 (9.4%) women with enrollment prehypertension or hypertension delivered an SGA neonate. Women with persistent hypertensive range blood pressures had an SGA rate 2–3 times higher than other women ( p = 0.272) as well as a significantly higher preeclampsia rate ( p < 0.001). Women with elevated enrollment blood pressures did not have an increased SGA rate if their blood pressures improved throughout pregnancy. Logistic regression identified enrollment uterine artery Doppler, pregnancy-associated plasma protein-A levels, and ethnicity as primary contributors to SGA. Conclusion : Blood pressure improvement throughout pregnancy decreases the preeclampsia rate without increasing SGA frequency. Theoretical risks of fetal growth delay should not prevent investigations into improved maternal blood pressure control, possibly at thresholds lower than commonly used in obstetric practice, beginning in the first trimester of pregnancy.